A survey on different PAPR reduction techniques in OFDM systems (International Journal of Engineering and Computer Science, 2016)
Orthogonal  Frequency Division Multiplexing  is considered as one of the most promising technology for future communication technology as it provides spectral efficiency robustness against multipath fading & avoids inter symbol interference. However one of the major drawbacks of OFDM system is high PAPR resulting in performance degradation of DAC & decreases efficiency of power amplifier. In this paper we review on OFDM system, its different types of PAPR  reduction techniques and comparison of different PAPR reduction techniques